Culicoides (Diptera: Ceratopogonidae) Communities Differ Between a Game Preserve and Nearby Natural Areas in Northern Florida. Issue 1 (3rd August 2020) - McGregor, Bethany L; Blackburn, Jason K; Wisely, Samantha M; Burkett-Cadena, Nathan D
Abstract: Culicoides Latreille biting midges are small hematophagous flies that feed on a variety of vertebrate animals. White-tailed deer ( Odocoileus virginianus ), a farmed species in the United States, can occur at high densities on farms. This elevated density of available hosts may result in greater abundance of midges and greater potential for disease transmission on farms than natural ecosystems. This research aimed to determine whether Culicoides abundance varied between a game preserve in Gadsden County, Florida, a site bordering the preserve ('adjacent'), a site 3.5 km away ('moderate'), and a site 13 km away ('distant'). CDC light traps were set one night per week at the preserve, adjacent site, and moderate site in 2016 and at all four sites in 2017. Total abundance was greatest at the preserve and second greatest at the adjacent site both years. Average abundance of female Culicoides stellifer (Coquillett) was an order of magnitude greater on the preserve ( x ¯ = 24.59 in 2016, 17.95 in 2017) than at any other site ( x ¯ ≤ 1.68 in 2016, x ¯ ≤ 1.03 in 2017), whereas the greatest average abundance of Culicoides venustus Hoffman was found at the adjacent site (x ¯ = 5.15 in 2016, x ¯ = 1.92 in 2017). Distance from the preserve significantly affected overall average abundance for both species ( P < 0.001), although pairwise significance varied. Species diversity was lowest on the preserve and highest at the moderate site both years. These data suggest that high densities of animals may increase transmission potential on high fence preserves and in adjacent areas by contributing to high densities of vector species.